The social rituals and their relation to the methods of using water in Algerian families A field study on a sample in families of the municipality of Bab El Oued and the municipality of Tamantit - chareuf, samira (Journal of Social Sciences and Humanities, 2021)
The social customs of water use are the key concept to interpreting how Algerians think and how do they tend to adapt in an environment dominated by belief and superstition. Indeed, these customs continued to exist from generation to another via socialization. Sometimes, they become practices characterized by tradition without knowing its real direction to protect the follower or a member of his family. In order to achieve the objectives of the study was based on the descriptive approach, comparative approach, and anthropological approach, apply the observation and interview tool. The study found the appearance: The folk rituals of the two municipalities show the use of water for bathing ritual, water sprinkling, as cites, marriage and circumcision, religious ceremonies; spinster woman, and traveling...etc. These behaviors remain a social heritage that link the past to the present to forms the identity of the society.